Diarrhea, Urosepsis and Hemolytic Uremic Syndrome Caused by the Same Heteropathogenic Escherichia coli Strain. Issue 9 (September 2016) - Ang, C. Wim; Bouts, Antonia H. M.; Rossen, John W. A.; Van der Kuip, Martijn; Van Heerde, Marc; Bökenkamp, Arend
Abstract : We describe an 8-month-old girl with diarrhea, urosepsis and hemolytic uremic syndrome caused by Escherichia coli . Typing of cultured E. coli strains from urine and blood revealed the presence of virulence factors from multiple pathotypes of E. coli . This case exemplifies the genome plasticity of E. coli and the resulting heteropathogenic strains.